(untitled) (Perner’s Contacts, 2021)
The paper deals with the issue of traffic calming on selected sections of local roads, which are located in the capital city of Prague. These are sections with monitored traffic intensity. On the given sections, a local survey and analysis of selected attributes (type of physical traffic calming measure, location, traffic intensity, etc.) took place. The paper also verifies hypotheses whether the location of selected physical calming elements on given sections is consistent (according to the type of measure and the cause of need) and whether their number depends on the value of traffic intensity or length of the section. The hypotheses of the dependence of the measure on the length of the section or the intensity were refuted, but the way to a possible expansion of the amount of data and their analysis to find more complex dependencies was outlined.